Simulation Tool for Queuing Models: QSIM - Saxena, Dr. Pratiksha; Sharma, Lokesh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper proposes simulation software QSIM (Queuing Simulation) to simulate queuing models. QSIM is a tool which simulates and compares the results of different queuing models. This tool is programmed in JAVA and is based on analytical approach to guide optimization strategy. In Qsim, Simulation is carried out by providing the inputs for arrival rate, service rate and number of servers and using these values the performance measurement of a particular model is stored in the database for further comparisons and study. Simulation results are stored in excel file and it also provides graphical results to compare the outcome.